Deep inelastic scattering off scalar mesons in the 1/N expansion from the D3D7-brane system - Jorrin, David Gustavo (2016)
Deep inelastic scattering (DIS) of charged leptons off scalar mesons in the 1/N expansion is studied by using the gauge/gravity duality. We focus on the D3D7-brane system and investigate the corresponding structure functions by considering both the high energy limit and the 1/N expansion. These limits do not commute. From the D7-brane DBI action we derive a Lagrangian at sub-leading order in the D7-brane fluctuations and obtain a number of interactions some of which become relevant for two-hadron final-state DIS. By considering first the high energy limit followed by the large N one, our results fit lattice QCD data within 1.27% for the first three moments of F2 for the lightest pseudoscalar meson.